Improving policy coherence in food, land, and water systems to advance sustainable development in India: a case study of Rajasthan - Council on Energy, Environment and Water (CEEW); International Water Management Institute (International Water Management Institute (IWMI). CGIAR Initiative on National Policies and Strategies, 2024)
The interconnections between food, land, and water (FLW) systems are intricate, and actions in one system can impact the other. The global need to ensure the sustainability of these systems has become markedly more urgent, necessitating further efforts towards achieving the Sustainable Development Goals (SDGs) related to sustainable agriculture, water management, land use, and climate action. India has made significant headway in achieving these SDGs while balancing its rapid economic development (Government of India 2024). This is evidenced by the country's substantial increase in agricultural productivity alongside environmental conservation efforts, as shown by the rise in Gross Value Added in agriculture per worker from 61,427 in 2015-16 to 87,609 in 2023-24, while simultaneously expanding protected areas from 5.14% in 2015 to 5.43% in 2023. The commitment to sustainable development is further demonstrated by the increased adoption of organic farming from 0.97% in 2015-16 to 4.43% in 2022-23, improved integrated water resources management (from a score of 45 in 2020 to 75 in 2023), while maintaining economic growth as reflected in the growing share of India's exports in global trade (Government of India 2024). Nevertheless, the complex and dynamic nature of these interconnections demands coherent policy efforts (CEEW and IWMI 2023).